Regulation of the CaV3.2 calcium channels in health and disease Regulácia CaV3.2 vápnikových kanálov v zdraví a chorobe - Lacinová Ľ. (European Pharmaceutical Journal, 2017)
Family of T-type or low-voltage activated calcium channels consists of three members: CaV3.1, CaV3.2, and CaV3.3. CaV3.2 channel has almost identical biophysical properties as the CaV3.1 channel, but is distinguished by a specific tissue expression profile and a prominent role in several pathologies, including neuropathic pain, epilepsy, and dysregulation of cardiac rhythm. Further, it may be involved in phenotype of autism spectrum disorders, and amyotrophic lateral sclerosis. It represents a promising target for future pharmacotherapies.